2017
DOI: 10.1016/j.brainres.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based therapies for the treatment of schizophrenia

Abstract: Schizophrenia is a devastating psychiatric disorder characterized by positive, negative and cognitive symptoms. While aberrant dopamine system function is typically associated with the positive symptoms of the disease, it is thought that this is secondary to pathology in afferent regions. Indeed, schizophrenia patients show dysregulated activity in the hippocampus and prefrontal cortex, two regions known to regulate dopamine neuron activity. These deficits in hippocampal and prefrontal cortical function are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…People with SZ have reduced stem cell proliferation in the dentate gyrus. Next, SZ patients demonstrate a reduced number of synapses between the hippocampal mossy fibers and pyramidal neurons, which is associated with changes in synaptic plasticity markers [17,18]. All above findings confirm the dysfunction of the hippocampus structure in SZ.…”
Section: Neuroanatomy Of Szsupporting
confidence: 63%
See 1 more Smart Citation
“…People with SZ have reduced stem cell proliferation in the dentate gyrus. Next, SZ patients demonstrate a reduced number of synapses between the hippocampal mossy fibers and pyramidal neurons, which is associated with changes in synaptic plasticity markers [17,18]. All above findings confirm the dysfunction of the hippocampus structure in SZ.…”
Section: Neuroanatomy Of Szsupporting
confidence: 63%
“…Therefore, it is considered that abnormal prefrontal cortex activity contributes to cognitive dysfunction observed in patients with SZ. Interestingly, the prefrontal cortex and hippocampus are connected neuronal systems and dysregulated prefrontal and hippocampal activity may underlie some of the symptoms of SZ [18].…”
Section: Neuroanatomy Of Szmentioning
confidence: 99%
“…Recently, these limitations have been addressed by advances in the xenotransplantation of cells and organoids differentiated from human PSCs. Given the recent explosion of cell-based therapies under investigation in the preclinical or clinical settings for many diseases [96][97][98][99][100] , iPSC-based chimaeric disease modelling by xenotransplantation has emerged as a reliable tool to fuel these advances by faithfully modelling human disease (Fig. 3, Box 1).…”
Section: Human-animal Chimaerasmentioning
confidence: 99%
“…These findings may be significant as interneuron dysfunction has been associated with a variety of neurodevelopmental and psychiatric disorders, including schizophrenia, autism, and intellectual disability (37). For example, schizophrenia patients have decreased expression of the GABA synthesizing enzyme, glutamic acid decarboxylase (GAD), in the prefrontal cortex, an effect that seems to reflect not a loss of cells but rather a loss of function in specific subclasses of interneurons (38). We have recently demonstrated that disrupting interneuron function in the cortex can produce schizophrenia-like deficits in social interaction and cognitive function in otherwise healthy animals (39).…”
Section: Prenatal Buprenorphine Exposure Alters Interneuron Migrationmentioning
confidence: 99%